The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.2134/jeq2004.1810
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Organic Carbon Dynamics and Cadmium Fate in Long‐Term Sludge‐Amended Soil

Abstract: A model is described that may help to resolve uncertainty and controversy over the long-term consequences of sludge applications to arable land, especially with regard to the effects of sludge adsorption characteristics on trace metal solubility and bioavailability (e.g., the sludge "time bomb" or sludge "protection" hypotheses). Mass balances of organic and inorganic material derived from sludge and crop residues are simulated. Each pool has a potentially different adsorption affinity for trace metals, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Increasing Cd input generally resulted in increasing Cd plant at three out of four sites. However, similar to Cd DGT , plant Cd uptake has been shown to vary widely with slight changes in soil physical and chemical parameters (Bergkvist and Jarvis, 2004 and Wang et al, 2006). …”
Section: Resultsmentioning
confidence: 94%
“…Increasing Cd input generally resulted in increasing Cd plant at three out of four sites. However, similar to Cd DGT , plant Cd uptake has been shown to vary widely with slight changes in soil physical and chemical parameters (Bergkvist and Jarvis, 2004 and Wang et al, 2006). …”
Section: Resultsmentioning
confidence: 94%
“…Not reaching the maximum copper concentration for both sewage sludges is an indication that sewage sludges adsorb a large quantity of copper and potentially other heavy metals. Bergkvist and Jarvis (2004) found that soils amended with sewage sludge have a very high adsorption capacity with regard to cadmium. Liu and Wang (2004) studied in situ speciation of copper-humic substances in a contaminated soil during electrokinetic remediation and found that copper-humic substances were associated with 50% of the total copper contained in the soil.…”
Section: Vol 171~no 1 Copper Mobility In Soil and Sewage Sludges 35mentioning
confidence: 99%
“…It is not clear to what extent preferential flow will contribute to metal leaching at the field scale. Bergkvist & Jarvis (2004) attributed the difference between modelled and observed Cd profiles in a well-structured clay loam soil, amended with sewage sludge, to the effects of macropore transport.…”
Section: Introductionmentioning
confidence: 99%